2007
DOI: 10.1021/jp070336w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Modelling of a New Tetramer Complex of Europium

Abstract: A new compound with the formula [Eu4(ETA)9(OH)3(H2O)3)], where ETA is ethyl 4,4,4-trifluoroacetoacetate, has been synthesized and investigated by photoluminescence spectroscopy. The compound was characterized by means of chemical analysis, vibrational (IR), UV-vis absorption, and luminescence spectroscopies, and X-ray crystallography. The crystal structure of the [Eu4(ETA)9(OH)3(H2O)3)] complex in the solid state, determined by X-ray diffraction analysis, revealed that it crystallizes in the triclinic crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…The coordination environment of the Eu(III) ion is asymmetry and have no inversion center, which can be confirmed by the appearance of the emission 5 D 0 → 7 F 0 (symmetry-forbidden) at 580 nm [24][25][26]. The intensity of 5 D 0 → 7 F 2 transition (electric dipole) is higher than the 5 D 0 → 7 F 1 transition (magnetic dipole), and the ratio of about 3.46 for I( 5 D 0 → 7 F 2 )/I( 5 D 0 → 7 F 1 ) further confirms the view above [27]. Interestingly, the very strong characteristic emission spectrum associated with the Eu(III) ion is observed, while the IN − based emission is absent.…”
supporting
confidence: 81%
“…The coordination environment of the Eu(III) ion is asymmetry and have no inversion center, which can be confirmed by the appearance of the emission 5 D 0 → 7 F 0 (symmetry-forbidden) at 580 nm [24][25][26]. The intensity of 5 D 0 → 7 F 2 transition (electric dipole) is higher than the 5 D 0 → 7 F 1 transition (magnetic dipole), and the ratio of about 3.46 for I( 5 D 0 → 7 F 2 )/I( 5 D 0 → 7 F 1 ) further confirms the view above [27]. Interestingly, the very strong characteristic emission spectrum associated with the Eu(III) ion is observed, while the IN − based emission is absent.…”
supporting
confidence: 81%
“…An X‐ray diffraction study revealed the presence of the nonanuclear mixed‐valent Eu III /Eu II cluster Eu 9 (μ 4 ‐OH) 2 (μ 3 ‐OH) 8 (bnac) 16 ( 5 ). A number of related penta‐, octa‐, and nonanuclear europium hydroxo cluster complexes containing β‐diketonate ligands have already been reported in the recent literature . The experimentally determined magnetic moments are μ/μ B = 3.36 ( 4 ) and also 3.36 for each Eu 3+ ‐ion in the nonanuclear compound 5 .…”
Section: Resultsmentioning
confidence: 93%
“…The 5 D 0 → 7 F 2 transition and 5 D 0 → 7 F 1 transition are electronic dipole transition and magnetic dipole, respectively, and the intensity of the former is stronger than that of the latter, which indicates that the coordination environment of the Eu(III) ion is asymmetric. [21] With excitation at 320 nm, the emission lines of complex 6 are respectively assigned to the 5 D 4 → 7 F 6 (489 nm) and 5 D 4 → 7 F 5 (545 nm) transitions of Tb(III) labeled in Figure 3c, and the fluorescence intensity at 545 nm is stronger. For complex 7, two characteristic bands excited at 311 nm can be seen in the emission spectra peaking at 482 nm and 574 nm, which are respectively attributed to transitions of 4 F 9/2 → 6 H 15/2 and 4 F 9/2 → 6 H 13/2 recorded in Figure 3d.…”
Section: Fluorescent Properties Of Complexesmentioning
confidence: 98%